An ICT Architecture for Managed Charging of Electric Vehicles in Smart Grid Environments - S. Bohn; M. Agsten; O. Waldhorst; A. Mitschele-Thiel; D. Westermann; P. Bretschneider (Journal of Engineering)
Growing shortage of fossil resources and an increasing demand of individual mobility worldwide require technology alternatives to existing mobility solutions. Electric vehicles (EVs) as one possible solution have moved into the focus of research and development. To maximize the positive environmental effect of EVs, it is proposed to charge them with respect to the availability of renewable energies. As the number of EVs will grow in the near future, their impact on the power distribution grid is no longer neglectable. Related research shows that unmanaged charging of EVs could result in overload situations or voltage instabilities. To overcome this, methods are proposed to manage the charging process holistically. Herein EVs become substantial elements of intelligent power grids (Smart Grids). As of today, research in the area of Smart Grids focuses mainly on either energy aspects or communication aspects while neglecting the interoperability of energy and communication related aspects. In this paper, an insight into Information and Communication Technology (ICT) aspects with respect to Managed Charging of EVs in Smart Grid environments will be given. Based on the use case of Managed Charging, requirements will be analyzed, results will be derived, and ICT solutions will be proposed with a set of recommendations for Smart Grid architectures.